2019
DOI: 10.30773/pi.2019.07.28
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological and Psychological Predictors of Social Functioning in Patients with Schizophrenia and Bipolar Disorder

Abstract: ObjectiveThe aim of this study is to examine social functioning in patients with schizophrenia and bipolar disorder and explore the psychological and neurophysiological predictors of social functioning. MethodsTwenty-seven patients with schizophrenia and thirty patients with bipolar disorder, as well as twenty-five healthy controls, completed measures of social functioning (questionnaire of social functioning), neurocognition (Verbal fluency, Korean-Auditory Verbal Learning Test), and social cognition (basic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 86 publications
3
19
0
Order By: Relevance
“…Deficits in social cognitive function are hallmarks of major psychiatric disorders, causing weakened social competence, impaired community functioning, and deterioration in quality of life (30,31). Relevant studies have investigated the impact of childhood trauma on social cognitive function (32)(33)(34). Our findings concur with the findings of Kilian, Asmal (17) that emotional neglect is negatively associated with social cognition within MCCB.…”
Section: Discussionsupporting
confidence: 89%
“…Deficits in social cognitive function are hallmarks of major psychiatric disorders, causing weakened social competence, impaired community functioning, and deterioration in quality of life (30,31). Relevant studies have investigated the impact of childhood trauma on social cognitive function (32)(33)(34). Our findings concur with the findings of Kilian, Asmal (17) that emotional neglect is negatively associated with social cognition within MCCB.…”
Section: Discussionsupporting
confidence: 89%
“…All patients completed the 14-week intervention group, which is consistent with a high acceptability of the treatment strategy. Our study on CPEGT supports the concept that specific psychosocial interventions targeting specific aspects of BD can be beneficial (72,73).…”
Section: Discussionsupporting
confidence: 81%
“…For instance, Jauregui et al 80 found that patients with SCZ displayed abnormal decreases in both HF-HRV and LF-HRV in response to a variety of social cognition tasks, as compared to HCs and unaffected first degree relatives. Similarly, in a recent 2019 study, social functioning in SCZ was negatively associated with the LF/HF ratio, which represents less flexibility in autonomic functioning 81 . Per the theory of neurovisceral integration 6 , deficits in PFC functioning, which has been related to reduced HRV, may lead to disinhibition of the amygdala and cardioregulatory regions in the medulla, thereby leading to increased heart rate and decreased HRV in situations of social or emotion processing (Fig.…”
Section: Implications Of Autonomic Dysfunction In Sczmentioning
confidence: 79%